Spiritual Issues and Challenges of Children with Cancer: Mothers’ Experience: Spiritual Issues and Challenges of Children with Cancer - Borjalilu, Somayeh (Bioethics and Health Law Journal (BHL), 2022)
Background and Aim: Cancer is a chronic disease and the second leading cause of death in children. In addition to clinical issues, challenges regarding spiritual issues exist. This study seeks to identify spiritual issues and challenges faced and experienced by mothers of children suffering from cancer. Methods: The current research was conducted using a phenomenological approach and content analysis. To gather information, 21 mothers were selected none randomly and were interviewed for a period of three months. Data were analyzed by comparing the responses of the interviewees constantly during the three months. Ethical Considerations: The study followed standard ethics guidelines concerning informed consent and confidentiality. Results: Seven themes were extracted via content analysis: philosophical questioning, faith and hope, relationship with nature, play and leisure, love and social support, expressing fear and anxiety and aggression, and expressing hope for the future. It was found that mothers were concerned about various philosophical questions raised by their children as well as issues regarding faith and belief and the quality of love, attention, and social support received. Conclusion: It is argued that empowering parents to play a more effective role in the spiritual care of children suffering from cancer may be a vital step in improving palliative care for these children as well as improving the psychological well-being of both cancer patients and their parents. Corresponding Author: Somayeh Borjalilu; Email: sborjalilu@gmail.com; ORCID: https://orcid.org/0000-0001-7348-0672 Please cite this article as: Borjalilu S. Spiritual issues and challenges of children with cancer: Mothers’ experience. Bioeth Health Law J. 2022; 2(1): 1-11 (e5). http://doi.org/10.22037/bhl.v2i1.19103